TOTAL PADATAN DAN WARNA KEFIR SUSU KAMBING DENGAN PENAMBAHAN EKSTRAK DAUN KELOR (Moringa oleifera L.) DENGAN PERSENTASE YANG BERBEDA - Inggit Alma Evita Yusuf; Triana Setyawardani; R Singgih Sugeng Santoso (Fakultas Peternakan Universitas Jenderal Soedirman, 2020)
Background. The purpose of this study is to know the effect of extract moringa addition (Moringa oleifera L.) on total solid of goat milk kefir to green color of goat milk kefir. Materials and methods. The materials were one liter of goat milk treatment, 12,5gr kefir seeds treatment and 1000ml of moringa leaf extract. Tools are jars, pans, stoves, ovens, refrigerators, scales, desiccators, colorimeters, 250 ml measuring cylinder, thermometers, erlenmeyer and porcelain cups. The study was carry out by the experimental method using a completely randomized design. The treatment tested were 250 ml goat milk and 1% moringa leaf extract (P1), 250 ml goat milk and 3% moringa leaf extract (P2), 250 ml goat milk and 5% moringa leaf extract (P3), 250 goat milk ml and 7% moringa leaf extract (P4). Results. The average total solid of kefir with the addition of Moringa oleifera L extract is between 15,09 ± up to 16,65% with no real effect. The average brightness color (L*) ranges from 67,36 to 69,62 while the reddish (a*) ranges from -1,84 to -2. The average yellowish color (b*) ranges from 5,54 to 6,16 no real effect.